On the Solvability of Discrete Nonlinear Two-Point Boundary Value Problems - Blaise Kone; Stanislas Ouaro (International Journal of Mathematics and Mathematical Sciences)
We prove the existence and uniqueness of solutions for a family of discrete boundary value problems by using discrete's Wirtinger inequality. The boundary condition is a combination of Dirichlet and Neumann boundary conditions.